Quantum Approximate Optimization Algorithm Pseudo-Boltzmann States - Díez-Valle, Pablo; Porras, Diego; García-Ripoll, Juan José (Physical review letters, 2023)
In this Letter, we provide analytical and numerical evidence that the single-layer quantum approximate optimization algorithm on universal Ising spin models produces thermal-like states. We find that these pseudo-Boltzmann states can not be efficiently simulated on classical computers according to the general state-of-the-art condition that ensures rapid mixing for Ising models. Moreover, we observe that the temperature depends on a hidden universal correlation between the energy of a state and the covariance of other energy levels and the Hamming distances of the state to those energies.